Quantitative proteomics and targeted metabolomics reveal the role of Cassia siamea L. extract in the response to high-fat diet-induced obesity in Drosophila - Ananya Dechakhamphu; Nattapong Wongchum; Theeraphan Chumroenphat; Alongklod Tanomtong; Sirithon Siriamornpun (Phytomedicine Plus)
Background: Cassia siamea L., an angiosperm native to Southeast Asia, has been traditionally used for various medicinal purposes, including antifever, antihypertensive, and antidiabetic applications. Despite its traditional use, limited scientific evidence supports its antiobesity properties. Purpose: This study aimed to investigate the antiobesity effects of C. siamea extract (CSE) both in vitro and in vivo. Methods: CSE was obtained via extraction from C. siamea wood with 70 % ethanol and its phytochemical content was analyzed by gas chromatography–mass spectrometry (GC‒MS) and high-performance liquid chromatography (HPLC). Drosophila was used to examine the effects of supplementation with C. siamea extract on lipase activity, body weight, triglyceride levels, physical strength, survival, and antioxidant activity in Drosophila fed a high-fat diet. Moreover, this study investigated the effects of the extract combined with a high-fat diet on amino acid metabolism and proteomic profiles to clarify its mechanism of action. Results: Syringic acid was the most abundant phenolic compound in CSE, followed by gallic acid, sinapic acid, protocatechuic acid, cinnamic acid, chlorogenic acid, and ferulic acid. In vitro, CSE significantly inhibited pancreatic lipase activity (IC50 = 67.73±3.24 µg/mL) in a noncompetitive manner. In a high-fat diet-fed Drosophila model, CSE supplementation (10 mg/mL) reduced lipase activity and triglyceride levels and improved body weight, suggesting antiobesity and potential antidiabetic effects. Additionally, CSE increased survival rates, physical strength, and antioxidant capacity, as evidenced by increased SOD1 activity and resistance to oxidative stress. CSE helped restore disrupted amino acid levels, particularly glutamine, alanine, and proline, indicating improved metabolic regulation. The results of the quantitative proteomics analysis indicate that a high-fat diet (HFD) alters proteins within metabolic pathways, which can be minimized in severity through CSE therapy. Conclusion: These findings highlight the potential therapeutic role of CSE in managing obesity and related metabolic disorders.